Geoplana multicolor Graff (Platyhelminthes: Tricladida): new records and taxonomic re-interpretation of morphological characters - Leal-Zanchet, Ana Maria; de Matos, Lisiane Bernardes (Zootaxa, 2011)
Many species of land flatworms have been described based on specimens, or even on a single specimen, from a sole locality. Thus, populational or individual variations are poorly known. The external morphology of Geoplana multicolor Graff, 1899 was first described based on a single specimen from the vicinities of the city of São Paulo, South Brazil. Marcus (1951) analysed specimens from São Paulo with a similar external aspect and considered them as conspecific with G. multicolor, describing their internal anatomy. In the present work, we amplify the known distribution of the species, by registering its occurrence in four localities of southern Brazil (state of Rio Grande do Sul), and comparatively analyse this relatively ample material, which includes different developmental phases. The description of histological aspects, especially those regarding musculature and secretory cells of the copulatory organs, has been enhanced and amplified after the present analysis. Thus, the description of G. multicolor is here complemented, with an improvement on the interpretation of important taxonomical characters. In addition, the paper reports, for the first time, the occurrence of an ejaculate attached to the atrial wall of a species of Geoplaninae which presents a penis papilla, and briefly discusses its significance.